Produtividade e rendimento industrial do milho doce irrigado em função de dose e parcelamento de nitrogênio - Cruz, Cláudia Amaral [UNESP] (2014)
The Brazil has hight potencial for producer sweet and unlike corn, there is little technical information. Aiming to evaluate the effect of nitrogen fertilization on productivity and industrial yield of sweet corn irrigated was developed an experiment in Guaíra, Brazil, in 04-22 to 08-15 of the 2013. The experimental design was a randomized blocks, in factorial design (6X2) with three replications. The treatments corresponding to six N dosage (0, 60, 120, 180, 240 and 300 kg ha- 1) and two ways of subdivisions: 0, 7,14, 21, 28, 35, 42 and 49 days after sowing (DAS) and 0,14, 28 and 42 DAS. These application times corresponded to vegetative stages, with application at sowing, VE, V3, V5 , V7, V9, V12 and V14 (eight subdivision) and seeding, V3, V7 and V12 (four subdivision), respectively. Maximum total and commercial cobs productivity of sweet corn, hybrid 'GSS 41240' are obtained with 300 kg ha-1of N. The largest number of nitrogen subdivisions does not contribute to increasing the productivity and industrial yield. The largest industrial yield, 0,293 kg of the grain by 1 kg of the cobs is obtained by applying of 188 kg ha-1 N